THE DEVELOPMENT INTEGRATED ENGLISH SYLLABUS FOR PHARMACY STUDENTS OF BENGKULU UNIVERSITY IN ACADEMIC YEAR 2021-2022 - Nike Puspita Sari; Hilda Puspita; Syahrial Syahrial (Universitas Bengkulu, 2022)
This study aimed to find out English skills that the student needs in Pharmacy classes at Bengkulu University and design the appropriate English syllabus for the students according to their needs. This research method applied research and development (R&D). The population of this research consisted of 350 Pharmacy students, 1 Pharmacy lecturer, 1 English lecturer and 2 Pharmacists. Random sampling was used to select a sample of 50 pharmacy students and the total sampling technique was to take 2 lecturers and 2 pharmacists. The data were collected from a questionnaire adapted from Jatmiko, S.B. (2016) and an interview. The researcher analyzed the data by counting the percentage. The results of this research showed that listening skills gained 23%, speaking skills gained 28%, reading skills gained 25% and writing skills gained 24%. From this data it can be seen that the highest percentage is in speaking, but the percentage among other skills is not much different. Therefore, it can be concluded that according to the results of data analysis, the syllabus is designed based on an integrated approach that has been validated and discussed with several experts. Based on the results of the data analysis, a syllabus was designed based on an integrated approach which has been validated and discussed with several experts. It is suggested that further researchers can develop English for pharmacy materials based on the integrated English syllabus from this study